What is Philosophical Ethology? - Marchesini, Roberto (Humanimalia, 2017)
In this paper, Marchesini engages first of all with both traditional and contemporary accounts of nonhuman subjectivity in order to show the untenability of such explanations based either upon an anthropomorphic “projection” of the human onto the nonhuman, or else upon a reductionist modeling of the animal as a machine. Ultimately, argues Marchesini, these explanations are founded upon a flawed principle of res extensa that can no longer be maintained. In order to place the question of animal subjectivity upon firm ground, Marchesini argues that it is necessary to move away from this Cartesian “automatism-based model,” and replace it instead with an “instrument-based model” that will better allow us to understand animal subjectivity — human and nonhuman — as emerging from within a complex neurobiological system that functions through specific activations of its systemic network structure. As such, he continues, subjectivity is necessarily situated, that is to say, every “subject” is an unpredictable manifestation of a unique and systemic state and emerging into being in accordance with the unique positional-relational state of the body in and of the here-and-now. Ultimately, Marchesini argues, all living beings share an emergent subjectivity, that the animal, be it human and/or nonhuman, is a subject because it exists, and as such does so not as a machine, but as a unique individual caught up in all the desires, emotions, feelings and memories that the world has to offer. (RI)